Processos de conceptualização do modelo cognitivo do país em usos da palavra Brasil - Vitor Cordeiro Costa (2022)
This thesis reports research aimed at describing and explaining conceptualization processes of the idealized cognitive model BRAZIL evoked by uses of the word ‘Brasil’. The research aimed specifically to: a) identify and explain how language structures are used to conceptualize the country and evoke its cognitive model; b) identify metonymic and metaphoric mappings established with BRAZIL; c) identify the frame elements ‘Brasil’ instantiates. Based on the central tenets of Cognitive Linguistics and Construction Grammar, the research was divided into three studies on the uses of ‘Brasil’ in two large corpora of Brazilian Portuguese (ptTenTen11 and Corpus Brasileiro), which provided empirical evidence for the conceptual processes. The general methodology relied on introspection and procedures from Corpus Linguistics, employing tools available on the Sketch Engine platform. It was observed that the BRAZIL model is rich in conceptually contiguous information, thus licensing a higher occurrence of metonymy. There were found 14 elements in 26 subcategories in the metonymic network evoked by ‘Brasil’. Results also showed that although ‘Brasil’ is traditionally considered a proper name, it occurs in the same constructions as common nouns, but triggers diverse conceptual processes. Two constructions were studied in greater detail, namely plural and the [um Brasil + adjective] adjunct construction. Besides metaphoric and metonymic processes, there were found ‘antimetonymic’ processes which create internal ‘discontiguity’ within the model of country. It is propounded that these processes can be better explained by associating Idealized Cognitive Models Theory and Construction Grammar. The thesis offers a test that enables to show how the same plural construction fused with names of countries can generate different conceptualizations depending on how the speaker categorizes the model and on the type of information present therein. The semi-fixed construction [um Brasil + adjective] is involved in a range of metaphoric and non-metaphoric conceptualizations and triggers processes of internal plurality, transformation through time, and image of the model BRAZIL. Through the observation of ‘Brasil’ and its collocates in the two corpora, it was found that the stronger collocations conceptualize ontological, deontic and modal dimensions; experiences involving movement, political and nationality bonds, helping and saving the country, travelling, and non-agency. It is proposed that referents categorized as COUNTRY are better understood if treated as cognitive models whose meanings are knowledge available at conceptual level.